Effects of 6 benzylaminopurine and meta topoline on micropropagation of Dendrobium chrysanthum Wall. ex. Lindl - Poeaim, A.; Kunwanlop, W.; Boonmee, W.; Laipasu, P. (My University, 2022)
The results of solid Gamborg's B5 medium at 2 mg/L mT found the highest average number of shoots at 1.6 shoots per explant; and the number of leaves at 3.7 leaves per explant. The concentration of 1.5 mg/L of mT showed the highest average length of shoots which was 9.82 mm, while the 0.5 mg/L mT revealed the most significant number of roots which were 0.9 roots per explant with the longest root of 3.75 mm. The liquid Gamborg's B5 medium showed the highest average number of shoots at 1.5 mg/L BAP, the same as at 1.5 mg/L mT. The medium without plant growth regulator and 1 mg/L mT was the highest average length of shoots of 13.98 mm. The highest number of roots per explant was 0.8, similar to 2 mg/L mT, but the different maximum length of roots of 3.04 mm. A hundred percent of protocorms induced shoots found in all media. The plantlets were survived after transplanting into pots and covered with plastic bags in four weeks.
Keywords: Dendrobium chrysanthum Wall. ex Lindl.; Mature seeds; Protocorms; Regeneration; Seed culture